Gender and the experience of moral distress in critical care nurses. (February 2015) - O'Connell, Christopher B
Background: Nursing practice is complex, as nurses are challenged by increasingly intricate moral and ethical judgments. Inadequately studied in underrepresented groups in nursing, moral distress is a serious problem internationally for healthcare professionals with deleterious effects to patients, nurses, and organizations. Moral distress among nurses has been shown to contribute to decreased job satisfaction and increased turnover, withdrawal from patients, physical and psychological symptoms, and intent to leave current position or to leave the profession altogether. Research question: Do significant gender differences exist in the moral distress scores of critical care nurses? Research design: This study utilized a quantitative, descriptive methodology to explore moral distress levels in a sample of critical care nurses to determine whether gender differences exist in their mean moral distress scores. Participants and research context: Participants ( n = 31) were critical care nurses from an American Internet nursing community who completed the Moral Distress Scale–Revised online over a 5-day period in July 2013. Ethical considerations: Institutional review board review approved the study, and accessing and completing the survey implied informed consent. Findings: The results revealed a statistically significant gender difference in the mean moral distress scores of participants. Females reported statistically significantly higher moral distress scores than did males. Overall, the moral distress scores for both groups were relatively low. Discussion: The findings of a gender difference have not previously been reported in the literature. However, other findings are consistent with previous studies on moral distress. Conclusion: Although the results of this study are not generalizable, they do suggest the need for continuing research on moral distress in underrepresented groups in nursing, including cultural and ethnic groups.